Bijak Berkomunikasi di Situs Jejaring Sosial: Tinjauan Etika dan Kebijakan Komunikasi - Agusly Irawan Aritonang (Jurnal InterAct, 2013)
Social media is a phenomenon in communication which is being most- discussed nowadays because social media phenomenon brings many great changes  and implications both in terms of how we communicate and the values related to communication, for example from the perspective of ethics. Benny Handoko‘s case shows how we need to use social media wisely so we are no longer entangled with a legal case. With the presence of UU ITE– Information  and  Electronic  Transaction  Regulation,  as  a  communication policy is expected to answer the need to facilitate the process of interactive media system, especially in the process of transactions using electronic data. However UU ITE itself gains criticism because of the overlap of the article of defamation characterin KUHP which eventually makes the guilty person gets more punishment; six years in jail or a fine of one billion Rupiah. This paper discusses the case of Benny Handoko‗s twitter from an ethics perspective in communication and communication policy.